In-Depth Characterization of the Effects of Cigarette Smoke Exposure on the Acute Trauma Response and Hemorrhage in Mice. Issue 1 (January 2019) - Hartmann, Clair; Gröger, Michael; Noirhomme, Jan-Philipp; Scheuerle, Angelika; Möller, Peter; Wachter, Ulrich; Huber-Lang, Markus; Nussbaum, Benedikt; Jung, Birgit; Merz, Tamara; McCook, Oscar; Kress, Sandra; et al.
ABSTRACT: Introduction: Hemorrhagic shock accounts for a large amount of trauma-related mortality. The severity of trauma can be further aggravated by an additional blunt chest trauma (TxT), which independently contributes to mortality upon the development of an acute lung injury (ALI). Besides, cigarette smoke (CS) exposure before TxT enhanced posttraumatic inflammation, thereby aggravating ALI. We therefore aimed to characterize the impact of an acute and/or chronic lung injury on organ dysfunction in a murine model of traumatic hemorrhagic shock (HS). Methods: After 3 weeks of CS exposure, anesthetized mice underwent HS with/without TxT. Hemorrhagic shock was implemented for 1 h followed by retransfusion of shed blood and intensive care therapy for 4 h including lung-protective mechanical ventilation, fluid resuscitation, and noradrenaline titrated to maintain mean arterial pressure ≥50 mmHg. Lung mechanics and gas exchange were assessed together with systemic hemodynamics, metabolism, and acid-base status. Postmortem blood and tissue samples were analyzed for cytokine and chemokine levels, protein expression, mitochondrial respiration, and histological changes. Results: CS exposure and HS alone coincided with increased inflammation, decreased whole blood sulfide concentrations, and decreased diaphragmatic mitochondrial respiration. CS-exposed mice, which were subjected to TxT and subsequent HS, showed hemodynamic instability, acute kidney injury, and high mortality. Conclusions: Chronic CS exposure per se had the strongest impact on inflammatory responses. The degree of inflammation was similar upon an additional TxT, however, mice presented with organ dysfunction and increased mortality rates. Hence, in mice the degree of inflammation may be dissociated from the severity of organ dysfunction or injury. Abstract : Supplemental Digital Content is available in the text